Influence of Body Composition on Lung Function and Respiratory Muscle Strength in Children With Obesity - Costa Junior, Dirceu (J Clin Med Res, 2016)
BACKGROUND: Obesity affects lung function and respiratory muscle strength. The aim of the present study was to assess lung function and respiratory muscle strength in children with obesity and determine the influence of body composition on these variables. METHODS: A cross-sectional study was conducted involving 75 children (40 with obesity and 35 within the ideal weight range) aged 6 - 10 years. Body mass index, z score, waist circumference, body composition (tetrapolar bioimpedance), respiratory muscle strength and lung function (spirometry) were evaluated. RESULTS: Children with obesity exhibited larger quantities of both lean and fat mass in comparison to those in the ideal weight range. No significant differences were found between groups regarding the respective reference values for respiratory muscle strength. Male children with obesity demonstrated significantly lower lung function values (forced expiratory volume in the first second % (FEV(1)%) and FEV(1)/forced vital capacity % (FVC%) : 93.76 ± 9.78 and 92.29 ± 3.8, respectively) in comparison to males in the ideal weight range (99.87 ± 9.72 and 96.31 ± 4.82, respectively). The regression models demonstrated that the spirometric variables were influenced by all body composition variables. CONCLUSION: Children with obesity demonstrated a reduction in lung volume and capacity. Thus, anthropometric and body composition characteristics may be predictive factors for altered lung function.